Treatment Trends and Outcome of Aneurysmal Subarachnoid Hemorrhage by Hospital Volume. (1st September 2019) - Lopez-Rivera, Victor; Lee, Songmi; Chen, Peng R; Blackburn, Spiros L; Rosenbaum-Halevi, David; Bambhroliya, Arvind; Vahidy, Farhaan; Savitz, Sean; Sheth, Sunil
Abstract: INTRODUCTION: With increasing availability of endovascular aneurysm treatment, more patients with aneurysmal subarachnoid hemorrhage (SAH) may be treated at lower-volume centers. In this nationwide observational cohort study, we determine treatment trends over time and their impact on SAH patient outcome. METHODS: Using data from the Nationwide Inpatient Sample (NIS, 2005-2015), we identified patients with aneurysmal SAH treated with either endovascular coiling (EC) or surgical clipping (SC). Patients with SAH from other causes, such as trauma or arteriovenous malformations, were excluded. Primary endpoint was in-hospital mortality and was assessed using multivariate logistic regression adjusted for age, comorbidities, and annual hospital SAH volume. Lower volume centers were defined as centers performing 10 or fewer annual SAH treatments. RESULTS: Among 105 557 patients with aneurysmal SAH from 2005 to 2015, 68% were female and the median age was 54 [IQR 46-64]. In total, 60% were treated with EC and 40% with SC. Over the time span of the study, the number of patients with SAH remained comparable (8798 vs 9833, 2005 vs 2015), and the number of hospitals treating SAH did not increase. Lower-volume hospitals were more likely to perform SC early in the cohort (32% EC vs 68% SC, 2005-2011) compared to later (72% EC vs 28% SC, 2012-2015). In adjusted logistic regression from data between years 2012 and 2015, we observed a continuous decline in the likelihood of in-hospital mortality with increasing annual SAH treatments, with a significant decrease among hospitals performing 12 or more cases per year (OR 0.74, CI 0.58-0.93, P  < .05). CONCLUSION: In this observational cohort, we found increasing numbers of patients treated with EC at lower volume centers over time. Increasing annual aneurysmal SAH treatment volume corresponded with decreasing in-hospital mortality.